Estudo da natureza de interações químicas do tipo calcogênio e halogênio mediante o estudo da estrutura eletrônica e da teoria quântica de átomos em moléculas - Pineda, Nahum Ramirez (2021)
In this work we present the results of a systematic analysis of the electronic structure of different chemical systems, through the Density Functional Theory (DFT), for the study of the nature of chemical bonds involving chalcogen and halogen atoms in the construction of complex inorganic networks. The Quantum Theory of Atoms in Molecules (QTAIM), that allows a topological analysis of the electronic distribution, was used as a tool to interpret the nature of the chemical bonds and geometrical structures. The results indicate the duality of the chalcogen atom (Se, Te) that presents metallic or non- metallic character depending on its chemical environment, with bondings in the transition region between shared ↔ closed-shell and total energy densities (H) that can be negative (metallic character) or positive (non-covalent type interaction). The interactions of non- covalent type, such as those of chalcogen and halogen type, were characterized and the topological parameters determined for different inorganic networks and complex materials based on selenium and tellurium atoms. The ability of selenite (SeO3 2-) and phenyltellurolate (PhTe-) clusters to act as a coordination base was characterized by establishing their topological parameters at the corresponding bonding critical points.